Contribution of Commuters and Transit Activities on The Road Transport Carbondioxides Emission in Surakarta - Himawan, Widhi; Sajidan, Sajidan; Sunarto, Sunarto; Setyono, Prabang; Nancy, Natasha; Wijayanti, Sovia (Faculty of Geography, Universitas Gadjah Mada, 2024)
Road transportation became a main contributor to the emissions of Surakarta City. The driving factor for these conditions is predicted to originate from massive commuting and transit activities. This research covered the administrative area of Surakarta City in July–August 2022. The aim of the research was to determine the impact of commuting and transit on carbon dioxide (CO2) emissions from Surakarta transportation and develop a spatial interpretation of the distribution of emissions. The emission estimation method uses a Tier 3 calculation approach using the Mobilev software. Estimation based on average daily traffic data for 24 hours as well as the character of the monitored path. The results of the study obtained an estimate of road transportation emissions for the City of Surakarta to reach 722795.3 tons of CO2 peryear. Commuter and transit activities contribute to 50.33% of total major road emissions or 133.77% of local vehicle emissions. Commuter and transit emissions in Surakarta City are dominated by private passenger cars (38.26%) and motorcycles (37.71%). Emission distribution shows a pattern of emission load that is greater on the city gate and transit lines than the central business district (CBD) area.